A 3D kinematical analysis of long jump in the "Gold meeting Rio of Athletics 2007" - Barros, R. M.; Mercadante, L. A.; Lara, J. P.; Sakalauskas, C. P.; Prudencio, M.; Cunha, S. A.; Russomano, T. G.; Misuta, M. S. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
Reliability of reactive strength index (RSI) and time to stabilization (TTS) was examined during three maximal effort depth jumps from 30cm (N=22). Measures of jump height (JH), ground contact time (CT), RSI and TTS were obtained and analyzed for reliability. The JH, CT and RSI were shown to be highly reliable from trial-to-trial (ICCsingle > 0.9). Time to stabilization was not reliable from trial-to-trial (ICCsingle < 0.5). The RSI can be used to monitor performance or to optimize the height of depth jumps. Results suggest that coaches utilizing these procedures with large numbers of athletes may be able to use a single measure of RSI rather than repeated trials. Time to stabilization reliability must be improved before attempting to use it to quantify the landing phase of plyometric exercises.